The Use of Multimodality Learning Approach in Teaching Descriptive Writing: Effects on Students’ Writing Ability - Lubis, Wildan Iskandar; Harahap, Cici Auliah; Septiani, Nabila; Maulana, Azril; Rahmadani, Nia (ITScience (Information Technology and Science), 2026)
This study is to describe the application of multimodality based learning approach in teaching writing descriptive text, the students` writing descriptive text ability before and after using multimodality based learning approach, then whether there is a significant effect of multimodality based learning approach on students’ writing descriptive text ability. The method used is the one group pre-test post-test experiment with a sample of 30 students (taken through purposive sampling from 174 students). Data were collected through observation and tests. The result show that the application of the multimodality based learning approach was score 88.5% (good category). The mean score of students’ writing descriptive text ability before and after using multimodality based learning approach were 38.40 (poor category) and 79.2 (good category). Then, there is a significant effect of multimodality based learning approach on students` writing descriptive text ability at the tenth grade of SMA Negeri 1 Padang Bolak Julu. because the table paired sample t-test pretest and pos-test is lower than 0.05(0.000<0.05). it means that hypothesis (Ha) is accepted.